2022
DOI: 10.1186/s13046-022-02293-6
|View full text |Cite
|
Sign up to set email alerts
|

Targeting autophagy in prostate cancer: preclinical and clinical evidence for therapeutic response

Abstract: Prostate cancer is a leading cause of death worldwide and new estimates revealed prostate cancer as the leading cause of death in men in 2021. Therefore, new strategies are pertinent in the treatment of this malignant disease. Macroautophagy/autophagy is a “self-degradation” mechanism capable of facilitating the turnover of long-lived and toxic macromolecules and organelles. Recently, attention has been drawn towards the role of autophagy in cancer and how its modulation provides effective cancer therapy. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(41 citation statements)
references
References 441 publications
0
41
0
Order By: Relevance
“…These results further indicated that NRF2 may serve different roles in the progression of PCa and was activated during PCa androgen-independent transformation. Despite that no autophagy-targeting drugs were approved for PCa therapy, several preclinical studies indicated the promising progression about the using of autophagy-related drugs in PCa [ 25 27 ]. For example, diosgenin has high antitumor activity in prostate cancer via inducing autophagy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results further indicated that NRF2 may serve different roles in the progression of PCa and was activated during PCa androgen-independent transformation. Despite that no autophagy-targeting drugs were approved for PCa therapy, several preclinical studies indicated the promising progression about the using of autophagy-related drugs in PCa [ 25 27 ]. For example, diosgenin has high antitumor activity in prostate cancer via inducing autophagy [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, a programmed cellular process, mainly contributes to the degradation and recycling of damaged cellular organelles and macromolecules ( Kimmelman and White, 2017 ; Li et al, 2020 ; Ashrafizadeh et al, 2022 ). Dysfunction of the autophagic process has been associated with the onset and development of many human chronic pathologies, such as cardiovascular, metabolic, and neurodegenerative diseases as well as cancer ( Francesca et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The role of autophagy in tumour development and its role in anti-tumour drug functionality are current popular topics of research. While, the role of autophagy in cancer is controversial and no consensus has been reached regarding the precise involvement of autophagy in cancer progression and inhibition [ 5 ]. When autophagy exerts a pro-survival role, its stimulation results in a decrease in apoptosis of cancer cells, paving the way for cancer progression [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…When autophagy exerts a pro-survival role, its stimulation results in a decrease in apoptosis of cancer cells, paving the way for cancer progression [ 6 ]. However, when autophagy possesses an anti-tumor role, its activation significantly enhances sensitivity of cancer cells to therapy [ 5 ]. In primary lung tumors, autophagy associated with drug resistance has been reported as a biomarker for subclassification, differentiation, and local metastasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation